Family’s Economic Problems, Environmental Stability &Youth Delinquency in Society: Sociological Perspectives - Abu Samah, Irza Hanie; Shamsudin, Abdul Shukor; Zuhaily, Mohd Sufino (2017)
The sociological perspective on youth delinquency has been widely discussed by researchers and sociologist.However, youth delinquency in the society remains constant and there is no one theory that can fit to fix the problem.This paper stressed on the youth delinquency in society that is explained through sociological theories with family’s socioeconomic status and environmental stability as factors to delinquent behaviors. This paper shows the link of theories of delinquent behavior with economic problems that causes instability in the environment.Nonetheless, the discussion provided in this study is limited towards family economic problems and environmental instability; therefore more aspect are required to further study the factors of youth delinquency as it is important for every country to have healthy youth and free from criminal activities for the future development of a country.